2010
DOI: 10.1111/j.1365-313x.2010.04267.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genomic analysis of Tunisian Medicago truncatula reveals candidates for local adaptation

Abstract: SUMMARYGenome-wide association studies rely upon segregating natural genetic variation, particularly the patterns of polymorphism and correlation between adjacent markers. To facilitate association studies in the model legume Medicago truncatula, we present a genome-scale polymorphism scan using existing Affymetrix microarrays. We develop and validate a method that uses a simple information-criteria algorithm to call polymorphism from microarray data without reliance on a reference genotype. We genotype 12 inb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…However, one of seven windows that fell into the lowest 1% of the distribution of both D T and θ W contains an early nodulin gene (ENOD93) (5), suggesting that this episode of selection may have been associated with host-rhizobia interactions. Genes previously identified as targets of selection in M. truncatula, including DMI1, a nodulation-related gene (3), as well as genes identified as possible targets of adaptation to saline environments in Tunisian populations of M. truncatula (35) were not located in chromosomal regions harboring unusual levels of diversity or skewed frequency distributions (i.e., D T ) in our sample. The lack of correspondence between this study and previous studies may not be surprising-the studies by De Mita et al (3) and Friesen et al (35) both sampled from geographically restricted locations, whereas our range-wide sample may be powerful for detecting species-wide sweeps but poorly suited for identifying genes involved in local adaptation to biotic or abiotic conditions.…”
Section: −8mentioning
confidence: 89%
“…However, one of seven windows that fell into the lowest 1% of the distribution of both D T and θ W contains an early nodulin gene (ENOD93) (5), suggesting that this episode of selection may have been associated with host-rhizobia interactions. Genes previously identified as targets of selection in M. truncatula, including DMI1, a nodulation-related gene (3), as well as genes identified as possible targets of adaptation to saline environments in Tunisian populations of M. truncatula (35) were not located in chromosomal regions harboring unusual levels of diversity or skewed frequency distributions (i.e., D T ) in our sample. The lack of correspondence between this study and previous studies may not be surprising-the studies by De Mita et al (3) and Friesen et al (35) both sampled from geographically restricted locations, whereas our range-wide sample may be powerful for detecting species-wide sweeps but poorly suited for identifying genes involved in local adaptation to biotic or abiotic conditions.…”
Section: −8mentioning
confidence: 89%
“…Previous research has demonstrated that three of the four populations (i.e. TN 1, 8 and 9) used in this study are genetically differentiated and linked by moderate levels of gene flow, but are locally adapted to soil salinity levels (Friesen et al 2010). Saline populations' environments have 14 times greater soil sodium and 4.6 times greater magnesium levels than non-saline populations' environments (Table S1 in Supporting Information).…”
Section: Methodsmentioning
confidence: 98%
“…Medicago truncatula Gaertn (Fabaceae) is a self-compatible annual plant from the Mediterranean region found in a range of environments including saline and non-saline soils in Tunisia (Lazrek et al 2009;Friesen et al 2010). The genotypes used in this study are part of a larger collection of 39 genotypes from two populations of saline origin [i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In the more closely related barley and wheat, only about one-third of the salinity-related expression responses were overlapping. Intraspecific variation in gene expression is also manifested in locally adapted populations of model plants (Baxter et al 2010;Friesen et al 2010).…”
Section: The Problem Of Organismal Integration In Saline Environmentsmentioning
confidence: 99%